2010
DOI: 10.1007/s10661-010-1369-8
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on the occurrence and behavior of carbamazepine (CBZ) in aquatic environment of Yangtze River Delta, China

Abstract: The occurrence and behavior of carbamazepine (CBZ) was investigated in aquatic environment of Yangtze River Delta, East China. The water samples were enriched by solid-phase extraction and analyzed by high-performance liquid chromatography with diode array detector. The validation of the analytical method included linearity (0.1-1 mg/L), recovery studies, and determination of limits of quantification. Limits of quantification of CBZ in various aquatic samples were in the range of 0.1-0.2 μg/L. CBZ was detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(26 citation statements)
references
References 36 publications
1
23
1
1
Order By: Relevance
“…When these sites in Shanghai compared with other regions of the world (Table 1), it was found that the levels of psychiatric pharmaceuticals in Huangpu River in our study were higher than those in Germany (Ternes et al, 2001;Hass et al, 2012) and France (Togola and Budzinski, 2008), but lower than those in USA (Kolpin et al, 2002). The concentration level of target analytes in the present research was consistent with findings in the main Chinese river Yangtze River (Zhou et al, 2011). Investigation was also within the range of those results reported in Spain (Mendoza et al, 2014).…”
Section: Distribution In Huangpu Riversupporting
confidence: 91%
“…When these sites in Shanghai compared with other regions of the world (Table 1), it was found that the levels of psychiatric pharmaceuticals in Huangpu River in our study were higher than those in Germany (Ternes et al, 2001;Hass et al, 2012) and France (Togola and Budzinski, 2008), but lower than those in USA (Kolpin et al, 2002). The concentration level of target analytes in the present research was consistent with findings in the main Chinese river Yangtze River (Zhou et al, 2011). Investigation was also within the range of those results reported in Spain (Mendoza et al, 2014).…”
Section: Distribution In Huangpu Riversupporting
confidence: 91%
“…PPCPs have been detected in the aquatic environment in different parts of China [20][21][22][36][37][38][39][40]. There is, however, a lack of a systematic investigation that provide a good overview of the concentrations and risks of PPCPs in the natural aquatic environment of different parts of China so far.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmaceuticals, as emerging pollutants in aquatic environments, have received much attention recently [1][2][3][4][5]. A large variety of pharmaceuticals, including β-blockers, sympathomimetics, antiphlogistics, lipid regulators, antibiotics and so on, have been frequently detected in aquatic environments at concentration levels up to micrograms per litre in Europe, North America and South Asia [2,6,7].…”
Section: Introductionmentioning
confidence: 99%